Post-surgical complications in patients operated of craniosynostosis. Five year study - Miguel Angel Cruz Díaz; Ángel Serafín Camacho Gómez; Carlos Javier Artiles Rivero; Ramón Sarduy Arana (Acta Médica del Centro)
Introduction: most corrective surgeries in patients with craniosynostosis are performed without major complications; Despite this, there are factors that negatively influence its correct evolution. Objective: to describe the postsurgical complications in patients operated on for craniosynostosis in the Province of Villa Clara. Methods: a retrospective, descriptive cross-sectional study was carried out from January 2018 to December 2022 in the Province of Villa Clara, the study population was made up of all patients operated on for craniosynostosis in the center during this period. The variables studied were the complications presented, the classification of the malformation according to the affected suture, the age at which the surgical intervention was performed, the surgical technique performed and the surgical time used. Results: the main complication was superficial infection of the surgical wound; Complications predominated in patients with scaphocephaly and in those in whom the surgical intervention occurred after 12 months of life. Patients who underwent craniectomy, morcellation and suturectomy as surgical techniques had a higher rate of complications, as did those whose surgical time was greater than one hour and 30 minutes. Conclusions: most complications were mild. The factors associated with the appearance of these complications were scaphocephaly-type deformities, surgical interventions in patients over 12 months of age and the performance, in all patients, of cranial remodeling techniques, which imply a longer surgical time.